DEVELOPMENT AND VALIDATION OF UV-SPECTROPHOTOMETRIC AND RP-HPLC METHODS FOR CURCUMIN-TOFACITINIB NANOCARRIERS: A NOVEL PLATFORM FOR ENHANCED BREAST CANCER THERAPY - WAGHMARE, SUCHITA; HUSSAIN, UJBAN MD; RAROKAR, NILESH; KHEDEKAR, PRAMOD (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this study is to develop and validate analytical techniques for the accurate quantification, stability assessment, and quality control of curcumin-tofacitinib-loaded nanocarriers (CS-TF-NCs). Methods: A new RP-HPLC (Reverse Phase-High Performance Liquid Chromatography) and UV-spectrophotometric method was developed and validated to quantify CS (Curcumin), TF (Tofacitinib), and CS-TF-NCs (Curcumin-Tofacitinib-Nanocarriers). UV-spectrophotometry detected λmax values of 426 nm (CS) and 286 nm (TF), and shifts to 287 nm and 421 nm for nanocarrier-loaded samples, with excellent linearity (R² = 0.9994) in the range of 5–25 μg/ml. RP-HPLC analysis was found to be very sensitive with low LOD (Limit of Detection) (LOD = 0.045 μg/ml) and LOQ (Limit of Quantification) (LOQ = 0.07 μg/ml). Recovery levels were between 97% and 99%, and retention times were 2.212 and 4.285 min for CS and TF, respectively. Results: CS and TF revealed λ max values of 426 nm and 286 nm by UV-spectrophotometry, with high correlation coefficients of R² = 0.9962 and 0.998. For CS-TF-NCs, the values were determined at 287 nm and 421 nm with a high R² = 0.9994 that validates linearity for the entire range of concentration of 5–25 μg/ml. Validation through RP-HPLC has exhibited good sensitivity, LOD being 0.045 μg/ml, and high precision (%RSD<1.5%). The nanocarriers were characterized by good solubility and sustained release profiles, giving recovery and retention times of 97–99% with 2.212 and 4.285 min for CS and TF, respectively. Conclusion: This work established CS-TF-NCs as a platform with the potential to deliver targeted, effective breast cancer therapy.